2005
DOI: 10.1245/aso.2005.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Axillary Evaluation in Neoadjuvant Chemotherapy Patients With Ultrasonography and Sentinel Lymph Node Biopsy

Abstract: Background: There is ongoing debate regarding the optimal sequence of sentinel lymph node (SLN) biopsy and neoadjuvant chemotherapy (CTX) for breast cancer. We report the accuracy of comprehensive pre-neoadjuvant CTX and post-neoadjuvant CTX axillary staging via ultrasound imaging, fine-needle aspiration (FNA) biopsy, and SLN biopsy. Results: Axillary staging was pathologically negative by pre-neoadjuvant CTX SLN biopsy in 53 cases (58%); these patients had no further axillary surgery. In 38 cases (42%), axill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 36 publications
1
37
0
6
Order By: Relevance
“…54 Many reports have described the role of US-guided FNA biopsy of axillary lymph nodes in directing the surgical treatment of patients with early stage breast cancer; however, only a few reports have illustrated its utility in patients selected to receive neoadjuvant chemotherapy. Khan et al 51 reported the value of a comprehensive approach to staging, including the evaluation of axillary and nonaxillary lymph nodes (including supraclavicular, infraclavicular, and internal mammary chain lymph nodes), before neoadjuvant chemotherapy. 51 Although preneoadjuvant lymph node staging cannot determine the full extent of axillary lymph node disease, it provides useful information for medical oncologists in planning chemotherapy regimens.…”
Section: Fna Of Lymph Nodes In Breast Cancer/krishnamurthymentioning
confidence: 99%
See 1 more Smart Citation
“…54 Many reports have described the role of US-guided FNA biopsy of axillary lymph nodes in directing the surgical treatment of patients with early stage breast cancer; however, only a few reports have illustrated its utility in patients selected to receive neoadjuvant chemotherapy. Khan et al 51 reported the value of a comprehensive approach to staging, including the evaluation of axillary and nonaxillary lymph nodes (including supraclavicular, infraclavicular, and internal mammary chain lymph nodes), before neoadjuvant chemotherapy. 51 Although preneoadjuvant lymph node staging cannot determine the full extent of axillary lymph node disease, it provides useful information for medical oncologists in planning chemotherapy regimens.…”
Section: Fna Of Lymph Nodes In Breast Cancer/krishnamurthymentioning
confidence: 99%
“…Khan et al 51 reported the value of a comprehensive approach to staging, including the evaluation of axillary and nonaxillary lymph nodes (including supraclavicular, infraclavicular, and internal mammary chain lymph nodes), before neoadjuvant chemotherapy. 51 Although preneoadjuvant lymph node staging cannot determine the full extent of axillary lymph node disease, it provides useful information for medical oncologists in planning chemotherapy regimens.…”
Section: Fna Of Lymph Nodes In Breast Cancer/krishnamurthymentioning
confidence: 99%
“…[1][2][3] For the evaluation of axillary lymph node metastases, various approaches and examination techniques have been proposed to improve the diagnostic accuracy of ultrasound (US), CT, positron emission tomography (PET), and other diagnostic modalities. [4][5][6][7][8][9][10][11][12][13][14][15] However, no defi nitive criteria have yet been established. Mammary gland CT can be performed with the patient in nearly the same position as that during surgery, and it is beginning to attract attention as a modality that permits the extent of the primary lesion and axillary lymph node metastases to be evaluated simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al reported the results of repeat SLNB for patients initially found to be node-positive by SLNB before NAC, indicating that the identifi cation rates and false-negative rates of repeat SLNB were 97% and 4.5%, respectively. 34 They reported that one-third of patients who were initially node-positive were subsequently proven to be node-negative, allowing for the avoidance of ALND. Consequently, it is possible that a signifi cant number of patients whose axillary diseases were eradicated by NAC can be spared ALND during defi nitive surgery after NAC.…”
Section: Repeat Sentinel Lymph Node Biopsy After Neoadjuvant Chemothementioning
confidence: 99%